PELAKSANAAN FUNGSI-FUNGSI MANAJEMEN DALAM LEMBAGA KEPENDIDIKAN ISLAM - Nurfaizin, Fikrial; Jabar, Jaja Abdul; Zohriah, Anis; Patimah, Siti (Indonesian Journal of Islamic Studies (IJIS), 2025)
In today's competitive era of globalization, management plays a strategic role in optimizing the performance of Islamic educational institutions to produce high-quality human resources. This study aims to examine the implementation of management functions—particularly the planning function—and their contribution to achieving educational goals. The planning function, which includes needs identification, vision and mission setting, goal determination, and evaluation, has been shown to enhance institutional effectiveness through optimal resource utilization, clear direction, and adaptability to change. Additionally, this research highlights the importance of leadership, innovative learning strategies, and the integration of technology as key factors in the success of educational management. Despite facing various challenges such as limited resources and resistance to change, educational institutions can overcome these obstacles through appropriate managerial strategies, stakeholder engagement, and continuous improvement. The findings of this study are expected to contribute to the development of more effective and responsive management practices within the context of Islamic educational institutions in Indonesia.